Evaluation of the effects of pet bottle fibers and fly ash as admixtures to the mechanical properties of concrete mixes - Cajuguiran, Gil Jose A. (2019)
Numerous waste materials are generated from industrial wastes such as Fly Ash and PET Bottles. The increasing awareness about the environment has tremendously contributed to the concerns related with disposal of the generated wastes. Waste utilization has become an attractive alternative to disposal. Research is being carried out on the utilization of waste products in concrete, concrete being the most versatile and used construction material. Concrete?s high compressive strength and workability has made its widespread use. It has major disadvantages that it is brittle and weak in tension. With this, researchers have tried to improve concrete even further. In this study the researcher utilized fly ash and PET bottle fibers to improve the mechanical properties of concrete. PET bottle fibers were mixed in 2% and 3% quantities based on the volume of the concrete mixture. While the fly ash was mixed in 20%, 30% and 40% based on the volume of the concrete mixture. Each mixture formula was cured for 10 days and their compressive strength and tensile strength were tested. The researcher observed that most of the samples have higher compressive strength than the normal concrete mix when up to fly ash is added to the mixture. Although compressive strength decreased when plastic fibers were added, some values are still above the compressive strength of the normal concrete mix. It is also noted that the tensile strength of all experimental are lower than the normal concrete mix. But there is a trend that the tensile strength is still increasing as more PET bottle fibers are added into the mixture. With the results, the researcher concluded that Compressive Strength increased when Fly ash is added. The tensile strength also increases as the amount of plastic fiber is increased.